Online Reviews by Beauty Vloggers of Local Lipsticks Product Impact on Purchase Intention - Elda Octaffiana; Filda Rahmiati; Genoveva Genoveva (Indonesian Marketing Journal, 2022)
Lipstick is a necessity for all women, yet many Indonesian women continue to favor international brands since they are more familiar. The local cosmetics business is rising fast, but it has obstacles, such as a strong demand for premium or high-brand cosmetics, such as Korean items, which remain popular among young women in Indonesia. Today, beauty vloggers are regarded as a reputable source of information on a certain cosmetics product. The purpose of this study is to explore the effect of competence, trustworthiness, and beauty on the purchase intention of a local lipstick product, as mediated by customer attitude and persuasive talents. This study adopts a quantitative methodology, gathering data using an online survey platform from participants (Google Form). Researchers collected 146 questionnaires from Greater Jakarta women who had viewed YouTube beauty vlogger reviews and reside in Jakarta. In this research, SEM-PLS is utilized to test hypotheses and analyze data. It has been discovered that knowledge, dependability, and beauty have a considerable impact on purchase intent, as mediated by consumer attitude. When a beauty vlogger recommends a local product's lipstick, persuasive talents have a large direct impact on consumer purchase intentions.